The effectiveness of vaccination, testing, and lockdown strategies against COVID-19 - Marlon Fritz; Thomas Gries; Margarete Redlin (International Journal of Health Economics and Management, 2023)
The ability of various policy activities to reduce the reproduction rate of the COVID-19 disease is widely discussed. Using a stringency index that comprises a variety of lockdown levels, such as school and workplace closures, we analyze the effectiveness of government restrictions. At the same time, we investigate the capacity of a range of lockdown measures to lower the reproduction rate by considering vaccination rates and testing strategies. By including all three components in an SIR (Susceptible, Infected, Recovery) model, we show that a general and comprehensive test strategy is instrumental in reducing the spread of COVID-19. The empirical study demonstrates that testing and isolation represent a highly effective and preferable approach towards overcoming the pandemic, in particular until vaccination rates have risen to the point of herd immunity.
Keywords: I18; C23; 330; Pandemics; COVID-19; Economics; Vaccination; Testing; Non-pharmaceutical interventions; Effectiveness